Hubungan Tingkat Pengetahuan Ibu Tentang Pemberian MP-ASI dengan Kejadian Diare pada Anak Usia 6-24 Bulan - Alvian Merza Radi Putra; Melania Wahyuningsih; Fajarina Lathu (HEALTH CARE : JURNAL KESEHATAN, 2020)
Diarrhea normally happens in children because of their weak resistance, they are susceptible to digestive tract infection. One of the factors that causes diarrhea in children is complementary feeding. Mothers’ role in complementary feeding is very important, mothers’ carefulness in complementary feeding will prevent digestive problems in children. This study aimed to determine the correlation between mothers’ knowledge about complementary feeding and diarrhea incidence in children aged 6-24 months at Pugeran, Maguwoharjo, Depok, Sleman, Yogyakarta. This was a quantitative observational analytic research with a cross sectional design. The population were 41 mothers who have children aged 6-24 months in July 2019 in Pugeran Maguwoharjo, Depok, Sleman, Yogyakarta. The samples were selected using a total sampling technique. The instruments used were questionnaires. The data collected were analyzed using Fisher’s exact test. Result showed that there were 28 mothers who had good knowledge (68.3%), whereas 13 mothers had sufficient knowledge (31.7%). There were 12 children (29.3%) who didn’t experience diarrhea with the last three months. The resulted p-value was higher than 0.05, namely 0.419. There was no correlation between mothers’ knowledge about complementary feeding and diarrhea incidence in children aged 6-24 months at Pugeran Maguwoharjo, Depok, Sleman, Yogyakarta.